2001
DOI: 10.1097/00007632-200104010-00027
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Atlantoaxial Rotatory Dislocation With Odontoid Fracture

Abstract: As the pivot of rotatory subluxation changed after odontoid process osteosynthesis, posterior C1-C2 arthrodesis was performed. The patient probably could have been treated in a single-stage procedure using posterior C1-C2 transarticular fixation with bicortical interspinous graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…3,4 Odontoid fractures represent 7% to 9% of traumatic cervical spinal fractures 5,6 and an association between odontoid fractures and rotatory dislocation of the atlantoaxial joint has been documented. [7][8][9] This patient differs from the one reported by Spoors et al 9 in that the direct lateral translocation and fixed nature of the injury necessitated surgical restoration of the normal atlantoaxial relationship, which resulted in complete neurological recovery. Goel et al described 24 patients with fixed atlantoaxial dislocation, 18 of whom were associated with os odontoideum or odontoid process fracture.…”
Section: Discussionmentioning
confidence: 57%
“…3,4 Odontoid fractures represent 7% to 9% of traumatic cervical spinal fractures 5,6 and an association between odontoid fractures and rotatory dislocation of the atlantoaxial joint has been documented. [7][8][9] This patient differs from the one reported by Spoors et al 9 in that the direct lateral translocation and fixed nature of the injury necessitated surgical restoration of the normal atlantoaxial relationship, which resulted in complete neurological recovery. Goel et al described 24 patients with fixed atlantoaxial dislocation, 18 of whom were associated with os odontoideum or odontoid process fracture.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand for type 1 or 2 lesions some authors advocate that since there is a strong tendency for recurrence an early fusion is warranted. 5,6,19 In our case after 15 days of cervical traction the patient was symptom free and comfortable. The subsequent CT with 3D reconstruction showed persistent unilateral subluxation although torticollis had resolved and the patient had full range of movements at the neck.…”
Section: Discussionmentioning
confidence: 46%
“…All cases reported in literature so far have had relatively good outcomes with only two partial neurological deficits observed in the bilateral subluxation type of lesions. 6,17,23 In fact it has been reported that only 16% of atlantoaxial injuries produce neurological deficit 18 mainly due to the wide dimensions of the upper cervical canal in respect to the lower c-spine. Secondly due to the red-flag symptoms (torticollis + neck pain) on presentation, there is a low miss rate of these injuries with immediate and adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical reduction and internal fixation are indicated in the following case : when conservative measures fail to reduce fixed AARD, in the case of re-dislocation and for highly unstable injuries 8,12) . AARF in combination with a C2 fracture is an extremely rare injury, and only 6 such cases have been reported in the literature 1,5,6,9,11) . Moreover, only 1 case of a traumatic AARF with accompanying odontoid and C2 superior articular facet fracture has been reported in the literature 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only 1 case of a traumatic AARF with accompanying odontoid and C2 superior articular facet fracture has been reported in the literature 11) . Fuentes et al 5) reported on a case of successful treatment of type II odontoid fracture combined AARF after surgical fixation and reduction of the odontoid fracture with C1-C2 transarticular fixation. Seybold et al 9) reported on a case of failed reduction of C2 articular facet fracture combined with AARF after traction and halo immobilization, and they proposed that only a closed reduction under general anesthesia with muscle relaxation led to reduction.…”
Section: Discussionmentioning
confidence: 99%